2021
DOI: 10.1007/s11104-021-05029-1
|View full text |Cite
|
Sign up to set email alerts
|

Divergent responses of plant biomass and its allocation to the altered precipitation regimes among different degraded grasslands in China

Abstract: Purpose Climate models predict shifts in precipitation patterns characterized by increased precipitation amount and decreased frequency for semi-arid grasslands in northeast China. However, under these novel climatic conditions, potential differences in plant biomass and its allocation among different degraded grasslands remain unclear.Methods We conducted a mesocosm experiment to test the effects of higher precipitation amount (increased by 50% from the long-term mean) and lower frequency (decreased by 50%) o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 51 publications
3
22
0
Order By: Relevance
“…For this study, several sites with three degradation levels (light, moderate and severe) were randomly selected for the construction of the mesocosm (Figure S1). Distances between sites were less than 2 km, ensuring the same original soil and vegetation type (Yang et al, 2022). We did not need permission for this fieldwork.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…For this study, several sites with three degradation levels (light, moderate and severe) were randomly selected for the construction of the mesocosm (Figure S1). Distances between sites were less than 2 km, ensuring the same original soil and vegetation type (Yang et al, 2022). We did not need permission for this fieldwork.…”
Section: Methodsmentioning
confidence: 99%
“…On the one hand, we preferred to reduce precipitation frequency as much as possible to investigate the effects of extremely lower frequency on coupling and functions, while ensuring that precipitation frequency was well within the range of documented rainfall regimes of the past 50 years in this region (Figure S3). On the other hand, to avoid drought‐induced plant mortality and to ensure that soil water content was above the permanent wilting point (about 5% in this study), seven rainfall events were identified as the minimum number of rainfall events possible (Meng et al, 2021; Yang et al, 2022). All mesocosms received 305 mm precipitation, which is the 50‐year mean for the experimental period.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations